Bioinformatics Analysis of Toxicity and Functional Properties of Plant-Derived Bioactive Proteins - Khatun, Most. Sharmin; Jahan, Afrin (Control Systems and Optimization Letters, 2024)
The main objective of this review is to discuss the biological activities of plants and their potential for therapeutic use, as well as to highlight the many kinds of bioactive proteins. Plant-derived bioactive proteins are essential because of their many functional qualities and health advantages in a variety of domains, including nutrition, medicine, and agriculture. Plant-derived bioactive proteins have attracted a lot of attention because of their potential as medicines and health advantages. To improve comprehension and application, this study uses bioinformatic tools to present a thorough analysis of the toxicity and functional properties of these proteins. We examine the variety of bioactive proteins originating from plants, emphasizing their functions in anti-inflammatory, anti-cancer, and antibacterial properties. We evaluate these proteins' structural characteristics, binding affinities, and processes of interaction with target molecules using sophisticated bioinformatics technologies. A particular focus is on assessing possible toxicity, using in silico predictive algorithms to detect side effects and guarantee safety in medicinal applications. We also go over how to anticipate the functional characteristics of novel bioactive proteins by integrating proteomic and genomic data. There are many tools such as BLAST, Clustal Omega, Inter Pro Scan for the analysis of bioinformatic data have been reviewed here. This study emphasizes how important bioinformatics is to understand the safety and therapeutic potential of bioactive proteins generated from plants, which opens the door to their optimal application in nutrition and medicine.